The Black Sea Matters Too: Understanding Türkiye’s Role in the Black Sea Region through the Turkish Straits According to Regional Security Complex Theory - Hart, Allison (AUC Knowledge Fountain, 2023)
This paper first establishes the Black Sea as a region according to regional security complex theory then defines Türkiye’s role within the region and the impact that the Turkish Straits have on maintaining regional security. Through constructivist approaches and regional security complex theory the paper critiques previously defined concepts pertaining to Türkiye’s role in the region and outlines perceived security threats within the Black Sea region. The use of threat perceptions as a means for analysis provides a unique constructivist approach on regional security complex theory allowing for a grounded research approach to regionalism in the Black Sea. The threat shared perceptions: (1) economic threats; (2) maritime security threats; (3) historic animosities; and (4) Russian expansion; were defined through 20 qualitative interviews that were done with policy makers and academics in the region. The paper is critical of the Eurocentric turn that regionalism has taken since the establishment of Regional Security Complex theory and the hegemonic concepts that are imposed on the Türkiye because of it. Further research on Türkiye’s role in the Black Sea region is needed and a continuation of grounded theory to prevent distant hyper-securitized narratives that have emerged through regional security complex theory that was once more grounded in socio-historical research. Keywords: Black Sea, Regions, Regionalism, Regional Security Complex Theory, Türkiye, Turkish Straits, Regional Security, Security, International Relations, Black Sea Region, Russia, Ukraine, Georgia, Romania, Bulgaria, littoral states, social constructivism, constructivism, RSCT, NATO, EU, threat perceptions, shared threat perceptions,